2011
DOI: 10.5194/tc-5-791-2011
|View full text |Cite
|
Sign up to set email alerts
|

Deriving mass balance and calving variations from reanalysis data and sparse observations, Glaciar San Rafael, northern Patagonia, 1950–2005

Abstract: Abstract. Mass balance variations of Glaciar San Rafael, the northernmost tidewater glacier in the Southern Hemisphere, are reconstructed over the period 1950-2005 using NCEP-NCAR reanalysis climate data together with sparse, local historical observations of air temperature, precipitation, accumulation, ablation, thinning, calving, and glacier retreat. The combined observations over the past 50 yr indicate that Glaciar San Rafael has thinned and retreated since 1959, with a total mass loss of ∼22 km 3 of ice e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 48 publications
2
35
1
Order By: Relevance
“…For the validation of the modeled climate data, several sources of measured meteorological data were available (here, the term‘modeled climate data’ is used to refer to the climate data that were used as input data for the mass balance modeling after the statistical downscaling detailed in section 2.1 and the subgrid parametrization explained in section 2.2): the Chilean Weather Service (DMC): Continuous data of temperature and precipitation with long‐time records although there are problems at some stations in the 2000s, the Chilean Water Directory (DGA): Precipitation data of mixed quality and record length, other sources: Including the Chilean Navy, the Argentine Weather Service and the measurements of Koppes et al [].…”
Section: Results and Validation Of The Downscalingmentioning
confidence: 99%
See 1 more Smart Citation
“…For the validation of the modeled climate data, several sources of measured meteorological data were available (here, the term‘modeled climate data’ is used to refer to the climate data that were used as input data for the mass balance modeling after the statistical downscaling detailed in section 2.1 and the subgrid parametrization explained in section 2.2): the Chilean Weather Service (DMC): Continuous data of temperature and precipitation with long‐time records although there are problems at some stations in the 2000s, the Chilean Water Directory (DGA): Precipitation data of mixed quality and record length, other sources: Including the Chilean Navy, the Argentine Weather Service and the measurements of Koppes et al [].…”
Section: Results and Validation Of The Downscalingmentioning
confidence: 99%
“…This can be explained by the different time span that was analyzed by Escobar et al [] (data from the 1960s to the 1980s) and the increase of accumulation that we observe in the 1990s in our modeled data (Figure ). An increase of accumulation in the 1990s and 2000s as compared to the second half of the 1970s and the 1980s has also been found by Koppes et al [] on the San Rafael Glacier.…”
Section: Discussionmentioning
confidence: 99%
“…Among other results, the paper reported higher amounts of ablation on the glacier tongues along the eastern side of Patagonia, and accumulation in excess of 20 mwe on the highest sections of the icefield. They also found that 50%–80% of calving fluxes were due to dynamics in the San Rafael glacier, broadly agreeing to previous studies [ Koppes et al ., ]. Schaefer et al .…”
Section: Modeling Andean Glaciers and Climate Changes At Specific Locmentioning
confidence: 99%
“…Schaefer et al [2013Schaefer et al [ , 2015 NPI and SPI Not used 6.5 Lapse rate used only for redistribution of temperature inside each 5 km gird-cell. Koppes et al [2011] San Rafael glacier 3.9 (snow) 6.6 (ice) After reviewing global approaches, we examined modeling studies incorporating all Andean glaciers as a regional entity. These studies are important because they allow adequate identification of heterogeneous glacier responses to changes in climate.…”
Section: Findings and Open Challengesmentioning
confidence: 99%
“…Flow velocity at Bridge Glacier is moderate due to gentle gradients in the lower reaches of the glacier, as well as a relatively narrow cross-sectional area. A gentle surface slope reduces the gravitational stresses, while narrow valley sidewalls constrict glacier flow by providing substantial lateral drag (Benn et al, 2007a;Koppes et al, 2011), both of which limit flow speeds. Near-terminus flow speeds at Bridge Glacier are 1 to 2 orders of magnitude smaller than those observed at larger tidewater calving glaciers in Patagonia and Alaska (Rivera et al, 2012;Koppes et al, 2011;Meier and Post, 1987;Motyka et al, 2003) and reflect a smaller mass turnover, similar to lake-terminating glaciers Mendenhall and Tasman (Boyce et al, 2007;Dykes et al, 2011).…”
Section: Controls On Calvingmentioning
confidence: 99%